Foot Length Growth as a Novel Marker of Early Puberty. (November 2019) - Balzer, Ben W. R.; Cheng, Hoi Lun; Garden, Frances; Luscombe, Georgina M.; Paxton, Karen T.; Hawke, Catherine I.; Handelsman, David J.; Steinbeck, Katharine S.
Foot growth is part of overall pubertal growth but its relation to other anthropometric and hormonal changes is unclear. Our objective was to determine how foot length changes relate to changes in other growth parameters (height and weight), Tanner stage, and serum hormones. Adolescents (n = 342) were recruited to a 3-year longitudinal cohort study, underwent annual anthropometric assessments (height, weight, and foot length), and provided self-rated Tanner staging. They also provided blood samples that were analyzed using liquid chromatography-tandem mass spectrometry for serum testosterone and estradiol and classified as pre-pubertal or pubertal based on circulating hormone levels. Average annual percent increase in foot length was greater for pre-pubertal adolescents compared with pubertal. Increased foot length was associated with increases in height, weight, Tanner stage, and serum hormones in males and pre-menarcheal females but not post-menarcheal females. Foot length offers a novel, noninvasive, cost-effective, and easily demonstrable marker of early pubertal changes.